ANALISIS PENGARUH DAMPAK PANDEMI COVID-19 TERHADAP POTENSI WISATA DESA PUCUNG - Harsono, Harsono (Jurnal Atma Inovasia, 2021)
The tourism industry is one of the most well-known and worldwide industrial fields, just like Indonesia. Tourism in Indonesia is certainly not less than other developing countries. Indonesia is included in the list of countries that have the a lot of intriguing tourist destinations which attract the attention of tourists. Daerah Istimewa Yogyakarta (DIY) is a city known for its various types of tourism, especially with very beautiful beaches, especially in Girisubo sub-district, Gunungkidul Regency. Pucung Village which is located in the area also has a very beautiful beach. Since there is a lot of tourism potentials here, it is not surprising that many local and foreign tourists come to see the natural beauty in Yogyakarta and this can also encourage sources of income. However, all these tourism activities must be temporarily suspended because throughout 2020 the world is being attacked by the Corona Virus Disease (COVID-19) outbreak. This research uses a qualitative descriptive approach with secondary data. This research was conducted in Pucung Village, Girisubo District, Gunung Kidul Regency, Central Java. The purpose of this paper is to identify the impact of Covid-19 on the tourism potential of Pucung Village. The results and discussion of this research is that the number of tourists visiting Gunungkidul Regency, especially Pucung Village, has decreased due to the Covid-19 virus pandemic, so there is a need for efforts to restore tourism in Pucung Village during the new normal period by following the recommended health protocols that are believed to be effective in preventing the transmission of the Covid-19 Virus.